The Relationship Between Personal Hygiene, Knowledge Level, and Residential Density with The Incidence of Pityrasis Versicolor in Students at The Al-Aziziyah Islamic Boarding School, West Lombok - Baiq Ratu Mulansari; Wiwin Mulianingsih; Herlinawati Herlinawati; Fahriana Azmi (Jurnal Biologi Tropis, 2026)
Pityriasis versicolor is a common superficial fungal infection in tropical regions, including Indonesia, with a high incidence among adolescents. Boarding school environments may increase the risk of infection due to factors such as personal hygiene, knowledge levels, and residential density. This study aimed to determine the relationships between personal hygiene, knowledge level, and residential density and the incidence of pityriasis versicolor among male students at Al-Aziziyah Islamic Boarding School in West Lombok. This quantitative observational analytic study used a cross-sectional design and involved 96 male students selected through stratified random sampling. The results showed a significant relationship between personal hygiene and the incidence of pityriasis versicolor (p = 0.003), as well as between knowledge level and the incidence of pityriasis versicolor (p = 0.001). However, no significant relationship was found between residential density and the incidence of pityriasis versicolor (p = 1.000). In conclusion, personal hygiene and knowledge level are significantly associated with the incidence of pityriasis versicolor, whereas residential density is not.